2016
DOI: 10.3762/bjnano.7.49
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale effects in the characterization of viscoelastic materials with atomic force microscopy: coupling of a quasi-three-dimensional standard linear solid model with in-plane surface interactions

Abstract: SummarySignificant progress has been accomplished in the development of experimental contact-mode and dynamic-mode atomic force microscopy (AFM) methods designed to measure surface material properties. However, current methods are based on one-dimensional (1D) descriptions of the tip–sample interaction forces, thus neglecting the intricacies involved in the material behavior of complex samples (such as soft viscoelastic materials) as well as the differences in material response between the surface and the bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The contact-resonance frequency and quality factor are often referred to as mechanical parameters. Although, there are methods to approximately calibrate for the Young’s modulus, they require a standard reference sample with similar properties to the unknown sample, and this includes the surface properties [ 51 ]. Additionally, polymer mechanical properties are very sensitive to the frequency of the measurement due to their viscoelasticity (rate-dependent behavior) [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…The contact-resonance frequency and quality factor are often referred to as mechanical parameters. Although, there are methods to approximately calibrate for the Young’s modulus, they require a standard reference sample with similar properties to the unknown sample, and this includes the surface properties [ 51 ]. Additionally, polymer mechanical properties are very sensitive to the frequency of the measurement due to their viscoelasticity (rate-dependent behavior) [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several FDC experiments have revealed that the approach and retraction sections of force-distance curves performed on mammalian cells do not overlap. 3,41,50 The hysteresis observed in a FDC is either a consequence the existence of energy-dissipation processes inside a material 59,60 or produced by the breaking of the plasma membrane. Force-distance curves acquired sequentially on a single cell are very reproducible, 3,41 therefore, we conclude that the hysteresis is dominated by dissipative processes occurring inside the cell.…”
Section: Mechanical Model Of a Living Cellmentioning
confidence: 99%
“…Among other issues, there is no established and generally accepted framework to measure the viscoelastic properties from AFM experiments. 1,6,8,[16][17][18][19][20][21] Bimodal AFM provides a very fast, high resolution and accurate method to map the elastic properties of polymers and biomolecules. 22,23 It has been applied to determine with very high spatial resolution the elastic modulus of a large variety of materials and macromolecules such as antibodies 24 and other proteins, [25][26][27] DNA, 28,29 cells, 30,31 bone microconstituents, 32 lipid bilayers, 33,34 self-assembled monolayers, 35,36 2D materials 37 or organic semiconductor devices.…”
Section: Introductionmentioning
confidence: 99%